Odpowiedź:
[tex]3)\\\\-2(y+2)(3-y)-2y(3y+2)+4(3-y)(y-4)=\\\\=-2(3y-y^2+6-2y)-6y^2-4y+4(3y-12-y^2+4y)=\\\\=-2(y-y^2+6)-6y^2-4y+4(7y-12-y^2)=\\\\=-2y+2y^2-12-6y^2-4y+28y-48-4y^2=-8y^2+22y-60\\\\\\dla\ \ y=0,5\\\\-8y^2+22y-60=-8\cdot0,5^2+22\cdot0,5-60=-8\cdot0,25+11-60=-2+11-60=\\\\=-62+11=-51[/tex]
[tex]4)\\\\-(2b+3)(4-b)-3b(2+4b)(3-2b)+3b(2b-3)=\\\\-(8b-2b^2+12-3b)-3b(6-4b+12b-8b^2)+6b^2-9b=\\\\=-(5b-2b^2+12)-3b(6+8b-8b^2)+6b^2-9b=\\\\=-5b+2b^2-12-18b-24b^2+24b^3+6b^2-9b=24b^3-16b^2-32b-12\\\\\\dla\ \ b=-0,5\\\\24b^3-16b^2-32b-12=24\cdot(-0,5)^3-16\cdot(-0,5)^2-32\cdot(-0,5)-12=\\\\=24\cdot(-\frac{1}{2})^3-16\cdot(-\frac{1}{2})^2-\not32^1^6\cdot(-\frac{1}{\not2_{1} })-12=\not24^3\cdot(-\frac{1}{\not8_{1}})-\not16^4\cdot\frac{1}{\not4_{1}}+16-12=[/tex][tex]=-3-4+16-12=-19+16=-3[/tex]